A Study on Woman Employees Satisfaction in Various Benefits Schemes Offered by the Information Technology Industry - Sundar, Dr. K.; Srinivasan, Dr. T. (International Journal of Advanced Science and Technology, 2019)
The various benefits offered by the company either statutorily or voluntarily help in no small measure not only to boost the morale of the employees but also to shore up the loyalty factor of the employees. Further some of the benefits like transport facilities, holiday home, promotion polices, crèche and lunch facilities facilitate greatly in work life balance. The fringe benefits offered by the company entice the work force to continue their stay for a longer period. Promotion practices contribute a great deal to retaining the talent with the company. The medical claim facilities aid in keeping the health of the employees in good order so that absenteeism is minimized. In short the various benefits offered by the company tone up the morale of the employee. In this context examination of employees satisfaction level in various benefits offered by the employer is taken up for analysis. The conclusion will be given.Key Words: Benefit Schemes, Employee Satisfaction, Information Technology Industry, Woman Employees.